Taxonomic Identification and Nutritional Analysis of Pterocladiella capillacea in Zhanjiang - Zhengwen Lv; Hongyan Cai; Nenghui Li; Hang Li; Jun Zeng; Kefeng Wu; Luming Deng; Huaqiang Tan; Hua Ye (Marine Drugs)
To evaluate the nutritional value and development potential of Pterocladiella capillacea in the marine environment of Naozhou Island, Zhanjiang, this study conducted species classification and identification, followed by an analysis of key nutritional components. The combination of morphological and molecular results confirmed the identification of the collected samples as P. capillacea. Further analysis showed that P. capillacea in Zhanjiang had a moisture content of 74.9% and a protein content of 24%. In comparison, the fat (0.4%) and carbohydrate (15.4%) contents were relatively low, with moderate ash (14.3%) and crude fiber (9.1%) content. It contains a diverse range of fatty acids, with saturated fatty acids accounting for 51.82% and unsaturated fatty acids accounting for 48.18% of the total. The amino acid composition was also diverse, with essential amino acids comprising 31.58% and flavor-enhancing amino acids constituting 54.85%. The minerals contained four major elements and four trace elements, while heavy metal levels were within safety limits, ensuring their edibility. In conclusion, P. capillacea is a high-protein, low-fat economic seaweed with a favorable amino acid and fatty acid composition, rich in minerals, and with significant nutritional and developmental potential. This study provides important data to support future research and utilization of this seaweed.